KEEFEKTIFAN PEMBELAJARAN MENULIS KARANGAN NARASI BERDASARKAN PENGALAMAN DENGAN TEKNIK CLUSTERING DAN TEKNIK MODELING PADA SISWA KELAS V SD - Hafsah Amiran Mangga; Munirah Munirah; Tarman A. Arif (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aims to demonstrate the effectiveness of clustering techniques and modelling techniques in learning to write narrative essays based on personal experience. From the results of preliminary observations, it was found that by using conventional methods, students' ability in learning to write narrative essays based on personal experience was still lacking. The use of clustering and modelling techniques in learning to write narrative essays based on personal experience was expected to have a significant influence. This type of research used quantitative research that was True Experiment Design with pre-test, post-test control group design. The research findings showed that an increase in students’ learning outcomes in the experimental class by using clustering techniques and modelling techniques. Based on the results of the study, it can be concluded that the use of clustering and modelling techniques in learning to write narrative essays based on personal experience had a significant effect.